Circadian rhythms in power output on a swim bench - Reilly, T.; Marshall, S. (Journal of Swimming Research, 1991)
Circadian variation in power output (as performed on a biokinetic swim bench) and its relation to circadian rhythms in body temperature and subjective alertness were measured in 14 competent swimmers at six equidistant times (starting at 2:00 hr) of the day. Peak and mean power on a 30 s test were noted. Subjective scale responses for alertness and pre-exercise rectal temperatures were recorded. Distinctive circadian rhythms for pulse rate, rectal temperature, alertness, and both power measures were exhibited. The general time for the peak values was after 16:00 hr. The difference between the highest and lowest values in the rhythm was 14% for mean power and 11% for peak power. It was suggested that the amplitude of circadian rhythms increases with the complexity of motor tasks because of the size of the values obtained. Implication: The circadian rhythm in power output on a swim bench was closely related to the rhythm for body temperature and alertness. The existence of these rhythms should be taken into account when planning strength and power training stimuli.